Report. National Closing Workshop of DeRISK SE Asia in Cambodia - Soksophors, Yim; Phanna, Khieng (2022)
This report documents the presentations and discussions held during the national closing workshop of DeRISK SE Asia in Cambodia. The project results and outcomes are adopted and continued under the CGIAR Initiative on Asian Mega Deltas implementation in Cambodia.